Dynamics of Tree-Type Robotic Systems - Shah, Suril Vijaykumar; Saha, Subir Kumar; Dutt, Jayanta Kumar; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2013)
This book addresses dynamic modelling methodology and analyses of tree-type robotic systems. Such analyses are required to visualize the motion of a system without really building it. The book contains novel treatment of the tree-type systems using concept of kinematic modules and the corresponding Decoupled Natural Orthogonal Complements (DeNOC), unified representation of the multiple-degrees-of freedom-joints, efficient recursive dynamics algorithms, and detailed dynamic analyses of several legged robots. The book will help graduate students, researchers and practicing engineers in applying their knowledge of dynamics for analysis of complex robotic systems. The knowledge contained in the book will help one in virtual testing of robot operation, trajectory planning and control.
1 Introduction -- 2 Dynamics of Robotic Systems -- 3 Euler-Angle-Joints (EAJs) -- 4 Kinematics of Tree-Type Robotic Systems -- 5 Dynamics of Tree-Type Robotic Systems -- 6 Recursive Dynamics for Fixed-Base Robotic Systems -- 7 Recursive Dynamics for Floating-Base Systems -- 8 Closed-Loop Systems -- 9 Controlled Robotic Systems -- 10 Recursive Dynamics Simulator (ReDySim) -- Appendices -- References.-Index.
Keywords: Engineering; Materials; Engineering; Robotics and Automation; Mathematical Modeling and Industrial Mathematics; Continuum Mechanics and Mechanics of Materials